2019
DOI: 10.1017/s0032247419000160
|View full text |Cite
|
Sign up to set email alerts
|

Cold, dark, and dangerous: international cooperation in the arctic and space

Abstract: This article compares Russian–Western cooperation in the Arctic and Space, with a focus on why cooperation continued after the 2014 annexation of Crimea. On the basis of this comparative approach, continued cooperation is linked to the following factors: (1) the Arctic and Space are remote and extreme environments; (2) they are militarised but not substantially weaponised; (3) they both suffer from ‘tragedies of the commons’; (4) Arctic and Space-faring states engage in risk management through international la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…I have carried this insight further in my own work, arguing that separation can prevent a disruption in one dimension of an interstate relationship from spreading to other dimensions (Byers, 2017). My previous research has revealed that this was what occurred in the Arctic and in Space after the annexation of Crimea (Byers, 2017;Byers, 2019).…”
Section: Complex Interdependence and International Lawmentioning
confidence: 85%
See 2 more Smart Citations
“…I have carried this insight further in my own work, arguing that separation can prevent a disruption in one dimension of an interstate relationship from spreading to other dimensions (Byers, 2017). My previous research has revealed that this was what occurred in the Arctic and in Space after the annexation of Crimea (Byers, 2017;Byers, 2019).…”
Section: Complex Interdependence and International Lawmentioning
confidence: 85%
“…However, the negotiators of the 1967 Outer Space Treaty were addressing very similar issues when they prohibited national appropriation of the Moon and other celestial bodies (Outer Space Treaty, 1967). In addition to the rules found in treaties and customary international law, a great deal of 'soft law' has been developed for the Arctic and for Space-in the form of guidelines, codes of conduct, and even 'soft treaties' that are legally binding but contain provisions that are ambiguous, qualified by non-obligatory language, or redundant (Byers, 2019). For example, the Arctic Council was created by a declaration rather than a treaty, while the challenge of Space debris is so far being addressed by guidelines adopted by the Inter-Agency Space Debris Committee and the UN Committee on the Peaceful Uses of Outer Space (Arctic Council, 1996;IADC, 2007;COPUOS, 2007).…”
Section: Complex Interdependence and International Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…Space scientific cooperation has not been disrupted by the geopolitical crises that erupted between the West and Russia. 24 In the same vein, this scientific diplomacy is an opportune instrument for Moscow. In the long term, this working cooperative link may in due course facilitate confidence-building with its Western partners.…”
Section: From the Iss To The Exomars Astrobiology Program: Cooperation With Europe At Risk?mentioning
confidence: 97%
“…Samtidig, i en nordområdekontekst med hensyn på utenrikspolitikk, bruker jeg dette begrepet i 9 Forestillingene om en ressurskrig i nord har derimot mer eller mindre blitt forkastet, gitt det faktum at havretten allerede gir de arktiske kyststatene suverene rettigheter i de fleste av disse områdene (Dodds & Nuttall, 2016;Tamnes & Offerdal, 2014). Faktisk er ressursgrunnlaget i Arktis ofte heller brukt som et argument for hvorfor kyststatene ønsker å samarbeide om regional utvikling (Byers, 2019;Lackenbauer, 2021;Østhagen & Rottem, 2020). 10 Se Tunsjø, 2018, for mer om dette samspillet.…”
Section: Utenrikspolitikk Som Balansekunst (2017-2021)unclassified